Fractured militancy : precarious resistance in South Africa after racial inclusion - Paret, Marcel (ILR Press, an imprint of Cornell University Press, 2022)
"This book examines the consequences of democratization and racial inclusion in South Africa through a study of local protest and collective organizing in four low-income and predominantly Black residential areas around Johannesburg"--